Impact of locoregional irradiation in patients with upfront metastatic head and neck squamous cell carcinoma. (June 2019) - Rambeau, A.; Bastit, V.; Thureau, S.; Thariat, J.; Moldovan, C.; Roge, M.; Babin, E.; Gery, B.; Di Fiore, F.; Florescu, C.; Clatot, F.
Highlights: Locoregional evolution leads to problematic symptoms in metasatic HNSCC. Use of locoregional irradiation (LRT) is frequent in upfront metastatic disease. Radical dose was not associated with better outcomes than palliative scheme. Stable disease/partial response to chemotherapy seems to be a situation for LRT. Abstract: Objective: To evaluate the frequency of use, modalities and potential interest of locoregional irradiation (LRT) in patients with upfront metastatic head and neck squamous cell carcinoma (HNSCC). Methods: Retrospective multicentric study. Were included all patients presenting an upfront metastatic HNSCC treated by platin-5FU- cetuximab based regimen, from 2008 to 2016. Patients with past history of cervical irradiation or HNSCC within the 5 years before metastasis diagnosis were excluded. Results: 65 patients were included. 25 patients (38%) presented a response or stable disease with chemotherapy. Forty-one patients (63%) underwent a locoregional irradiation: 5 patients before chemotherapy (upfront RT), 13 patients with stable disease or response after chemotherapy (consolidation RT), and 23 patients with progressive disease. Median overall survival (OS) was 11.6 months, median progression free survival was 7.9 months. OS was significantly improved for patients who underwent LRT (median OS 16.1 vs 7.5 months, p < 0.01). Among patients who received LRT, OS trended to be better if LRT was performed as consolidation RT compared to upfront RT (median OS of 22.1 vs 15.5 months, p = 0.11). Among patients with stable disease or response after chemotherapy, there was a non-significant better OS for the 13 patients treated by LRT (median OS 22.1 vs 11.8 months, p = 0.21)). Radical dose was not associated with better locoregional control compared to palliative dose (p = 0.37). Conclusion: LRT is frequently performed during management of upfront metastatic HNSCC and associated with better OS. Non-progressive disease after firs-line chemotherapy seems a good way to select patients who would benefit from radical LRT.